A Feedback System for Assessing Human Condition Based on Keyboard Usage Activity - Danting, Ма; Shichkina, Yulia (Computer Tools in Education, 2024)
This paper proposes a model for assessing a person’s emotional state based on their interaction with a computer keyboard. The model integrates a feedback mechanism, which significantly improves the accuracy of predicting a person’s emotional states. Through systematic analysis of the dynamics of keyboard usage activity and observation of individual environmental factors, the proposed approach not only predicts the state of the keyboard user but also adapts to changes in their behavior. The results of testing the model using specially developed software confirmed its effectiveness. Feedback-based systems improve human interaction with intelligent systems, contribute to the development of intelligent systems and humans. The obtained results confirm the necessity and direction for improving the human-machine interface and serve as a basis for their future integration into more complex systems for assessing the psycho-physiological state of a person.